The effect of various pre-cured temperature of different resin materials on the degree of conversion and microhardness of cured composite resin - Manal A. Sultan (University of Mosul, College of Dentistry, 2014)
Aims: The aims of this in vitro study were to evaluate the effect of different temperatures of the pre- cured composite resin materials on the degree of conversion and knoop microhardness of cured composite resin. Materials and Methods : A forty five disc-shaped specimens were prepared from ( Ceram X, shade D2, Dentsply/ Caulk, USA) after stored for 24h in different temperatures ( 5,25,and 37°C) were light cured for 40s. The FTIR test was used to measure the degree of conversion for each specimen. The knoop microhardness was measured by the use of (WOLPERT-WERKE-GMBH Baujahr Testor, GERMANY) (Vickers hardness test) for each specimen. Data obtained was analyzed using one-way analysis of variance (ANOVA) and Duncan's test at a 0.05 significance level.Results : The statistical analysis of the results (ANOVA) showed that there was statistically significant difference in the degree of conversion and in the microhardness of the prepared samples at the different temperature. As the temperature of the composite resin increase, there was an increase in the degree of conversion and increase in the micro hardness of the samples.Conclusions : The use of pre-warmed composite resin may help to improve the degree of conversion and the micro hardness of composite resin especially at the deeper areas of a restoration which could result in an increase in the expected life of a composite restoration.